The Fall and Rise of Mid-Century Student Health Activism: Political Repression, McCarthyism, and the Association of Internes and Medical Students (1947–1953). (29th April 2019) - Chowkwanyun, Merlin
Abstract: Common narratives about the mid-century American medical profession's stunning rise forget a key element: political repression. During the 1940s and 1950s, the American Medical Association (AMA) and its allies sought to eliminate those who questioned American medicine's status quo, in particular opposition to national health insurance (NHI) and condoning of racism within its ranks. One casualty was the Association for Internes and Medical Students (AIMS), which into the 1940s, was the most prominent vehicle for medical student and trainee political organizing in the United Status. This article tells the story of its rapid demise in the era of McCarthyism at the hands of an AMA campaign to besmirch AIMS's name, and in the process, destroy it.